Meeting the vocational support needs of individuals with Asperger syndrome and other autism spectrum disabilities. - Müller E; Schuler A; Burton BA; Yates GB (Journal of Vocational Rehabilitation, 2003)
The purpose of this pilot study was to seek consumer perspectives on strategies for improving vocational placement and job retention services for individuals with Asperger Syndrome and other autism spectrum disabilities (ASDs). For this purpose, 18 adults with ASDs were individually interviewed about their experiences within the workplace. Participants were asked to (a) describe positive and negative aspects of their vocational experiences, (b) identify major obstacles to successful employment, and (c) recommend appropriate vocational supports to be provided by vocational rehabilitation counselors, employers and co-workers. Qualitative analyses of the interview transcripts revealed a number of common experiences and concerns which suggest the needs of individuals with ASDs should be recognized as different from others with more generalized developmental disabilities and/or mental retardation.